Gyp1 has a dual function as Ypt1 GAP and interaction partner of Atg8 in selective autophagy. Issue 6 (3rd June 2019) - Mitter, Anne Lisa; Schlotterhose, Petra; Krick, Roswitha
ABSTRACT: Macroautophagy/autophagy is a highly conserved intracellular vesicle transport pathway that prevents accumulation of harmful materials within cells. The dynamic assembly and disassembly of the different autophagic protein complexes at the so-called phagophore assembly site (PAS) is strictly regulated. Rab GTPases are major regulators of cellular vesicle trafficking, and the Rab GTPase Ypt1 and its GEF TRAPPIII have been implicated in autophagy. We show that Gyp1 acts as a Ypt1 GTPase-activating protein (GAP) for selective autophagic variants, such as the Cvt pathway or the selective autophagic degradation of mitochondria (mitophagy). Gyp1 regulates the dynamic disassembly of the conserved Ypt1-Atg1 complex. Thereby, Gyp1 sets the stage for efficient Atg14 recruitment, and facilitates the critical step from nucleation to elongation of the phagophore. In addition, we identified Gyp1 as a new Atg8-interacting motif (AIM)-dependent Atg8 interaction partner. The Gyp1 AIM is required for efficient formation of the cargo receptor-Atg8 complexes. Our findings elucidate the molecular mechanisms of complex disassembly during phagophore formation and suggest potential dual functions of GAPs in cellular vesicle trafficking. Abbreviations AIM, Atg8-interacting motif; Atg, autophagy related; Cvt, cytoplasm-to-vacuole targeting; GAP, GTPase-activating protein; GEF, guanine-nucleotide exchange factor; GFP, green fluorescent protein; log phase, logarithmic growth phase; NHD, N-terminal helical domain; PAS, phagophore assembly site; PE, phosphatidylethanolamine; PtdIns3P, phosphatidylinositol-3-phosphate; WT, wild-type